A Tour Guide's Performance Model for Sustainable Heritage at Borobudur - Hardani, Putu; Damanik, Janianton; Subejo; Suprihanto, John (Media Konservasi, 2024)
Expanding the workforce in the tourism sector is a key aspect of the Rebuild Tourism for the Future via Sustainable Development initiative of which tour guides may become an essential part. Tour guide positions involve providing detailed explanations about heritage attractions and instructing tourists on acceptable behaviour during their investigation of these sites. This research is significant because tour guides play a crucial role in the preservation of tourism by safeguarding cultural treasures. Research on tour guides involves analyses that explore the subject from the viewpoints of their function, history, and structure. This study aims to enhance our understanding of the ecology of the tourism industry and heritage destinations by developing a model for the competent development of tour guides at Borobudur. Data was collected through participatory observation and in-depth interviews with six tour guides in Borobudur who are members of the Indonesian Tour Guides Association. The data were examined utilising Atlas Ti version 9. The study's findings suggest that implementing a high-quality curriculum and training programmes could lead to an exceptional performance model for tour guides at the Borobudur. The curriculum encompasses the implementation of four key components: (1) the scope of study, (2) content standards, (3) the teaching process, and (4) the assessment process. On the other hand, the training aspect covers four elements: (1) training needs, (2) types of training, (3) trainers, and (4) evaluation